Formation of CYP3A‐specific metabolites of ibrutinib in vitro is correlated with hepatic CYP3A activity and 4β‐hydroxycholesterol/cholesterol ratio. Issue 2 (23rd November 2022) - Lee, Jonghwa; Fallon, John K.; Smith, Philip C.; Jackson, Klarissa D.
Abstract: Ibrutinib is an orally administered Bruton's tyrosine kinase inhibitor approved for the treatment of B‐cell malignancies, including chronic lymphocytic leukemia. Ibrutinib is metabolized primarily via oxidation by cytochrome P450 (CYP) 3A4/5 to M37 (the primary active metabolite), M34, and M25. The objectives of this study were to assess the relationship between formation of the major CYP3A‐specific ibrutinib metabolites in vitro and hepatic CYP3A activity and protein abundance, and to evaluate the utility of the endogenous CYP3A biomarker, plasma 4β‐hydroxycholesterol (4β‐HC) to cholesterol ratio, to predict ibrutinib metabolite formation in individual cadaveric donors with matching hepatocytes. Ibrutinib (5 μM) was incubated with single‐donor human liver microsomes ( n = 20) and primary human hepatocytes ( n = 15), and metabolites (M37, M34, and M25) were measured by liquid chromatography‐tandem mass spectrometry analysis. CYP3A4/5 protein concentrations were measured by quantitative targeted absolute proteomics, and CYP3A activity was measured by midazolam 1′‐hydroxylation. Ibrutinib metabolite formation positively correlated with midazolam 1′‐hydroxylation in human liver microsomes and hepatocytes. Plasma 4β‐HC and cholesterol concentrations were measured in plasma samples obtained at the time of liver harvest from the same 15 donors with matching hepatocytes. Midazolam 1′‐hydroxylation in hepatocytes correlated with plasma 4β‐HC/cholesterol ratio. When an infant donor (1 year old) was excluded based on previous ontogeny studies, M37 and M25 formation correlated with plasma 4β‐HC/cholesterol ratio in the remaining 14 donors (Spearman correlation coefficients [ r ] 0.62 and 0.67, respectively). Collectively, these data indicate a positive association among formation of CYP3A‐specific ibrutinib metabolites in human hepatocytes, hepatic CYP3A activity, and plasma 4β‐HC/cholesterol ratio in the same non‐infant donors.